Generic names for the mbira - Kubik, Gerhard (International Library of African Music, 1965)
I found the mbira to be an important instrument in Angola, where it occurs in at least four varieties. Generic names in Angola usually belong to the SANZHI group. The SANZHI area has to be widely extended. It covers all Angola and the north-eastern part of the Okavango district in South West Africa.
Keywords: Ethnomusicology; Mbira; Musical instruments; Mbira music; Angola; African Music; Mbira (Instrument)